(untitled) (Trabalho & Educação, 2018)
This paper refers to an already completed master’s degree research that sought to analyze the implantation of the Program for the Access to Technical Education and Employment (PRONATEC) in the IF Sudeste MG - Campus Muriaé and the role of the intellectuals who led the program in the period from 2012 to 2016. In addition to what is set, it considers that it is in the professionals’ performance that the key to the development of the policy is, and may or may not contribute to the maintenance of hegemonic interests. Methodologically it was used: the bibliographic research, the documentary analysis of Resolution CD / FNDE Nº. 04 of March 16, 2012, which establishes the regulations for the execution of PRONATEC, the reports of the National System of Information of Vocational and Technological Education - SISTEC, The Worker Training Grant, the PRONATEC FIC course guide and interviews with professionals who worked on the program at the Muriaé Campus through Fairclough’s Critical Discourse Analysis (ADC). As a reference of the main analysis it was used Gramsci (2001) as a guide to the concepts of education, intellectuals and hegemony. It was concluded, among other things, that PRONATEC policies studied at Muriaé campus seem to have much more objectives in terms of reproducing the rationalities of corporate capitalism than in the needs of permanent and solid professional training of workers. ___ Este trabalho refere-se a uma pesquisa de mestrado já concluída, que buscou analisar a implantação do Programa de Acesso ao Ensino Técnico e Emprego (PRONATEC) no IF Sudeste MG - Campus Muriaé e a percepção dos intelectuais que protagonizaram o programa, no período de 2012 a 2016. Para além do que está posto, considera-se que é na atuação dos profissionais que está a chave para o desenvolvimento da política, podendo colaborar ou não para a manutenção dos interesses hegemônicos. Metodologicamente foi utilizado: a pesquisa bibliográfica, a análise documental da Resolução CD/FNDE nº 04 de 16 de março de 2012, que estabelece a regulamentação para execução do PRONATEC, os relatórios do Sistema Nacional de Informações da Educação Profissional e Tecnológica (SISTEC), o documento referência da Bolsa Formação Trabalhador, o guia de cursos de Formação Inicial Continuada (FIC) do PRONATEC e entrevistas realizadas com nove servidores efetivos, do Campus Muriaé, que atuaram no programa por meio da Análise de Discurso Crítica (ADC) de Fairclough. Como referência de análise principal utilizou-se Gramsci (2001) para guarida nos conceitos de educação, intelectuais e hegemonia. Concluiu-se, dentre outras coisas, que as políticas do PRONATEC, estudadas no campus Muriaé, parecem ter seus objetivos muito mais em necessidades de reprodução das racionalidades do capitalismo-empresariado que propriamente nas necessidades de formação profissional sólida e permanente dos trabalhadores.